Intervensi Strategi Pemasaran Dalam Keputusan Pembelian Produk Kosmetik - Gafar, Abdul; Husni, M Fahrul (Sekolah Tinggi Ilmu Ekonomi (STIE) Tri Dharma Nusantara Makassar, 2024)
This study aims to analyze the influence of product quality and buying interest on the purchase decision of cosmetic products. Using a quantitative methodology, data is collected through surveys filled out by consumers of cosmetic products. Data analysis was carried out using statistical techniques to test two main hypotheses: first, that product quality has a positive and significant effect on purchasing decisions; Second, buying interest also has a positive and significant influence. The study results show that both variables, product quality and buying interest, significantly influence purchasing decisions. Product quality is an important factor influencing consumer perception and purchasing decisions. Meanwhile, buying interest, which is influenced by factors such as brand awareness and marketing, also plays an important role in driving purchasing decisions. Based on the results of this study, it is recommended that companies in the cosmetics industry focus their efforts on improving product quality and adopt effective marketing strategies to increase buying interest. This strategy must include product innovations that suit the needs and preferences of current consumers and the use of digital technology in marketing to attract and retain consumers. The conclusion of this study provides important insights for cosmetics industry players in developing effective business strategies to increase sales and customer loyalty